A 15-year-old boy with huge facial swelling, recurrent severe epistaxis, progressive proptosis, nasal obstruction and impaired hearing on right side - Asaduzzaman, Md.; Alam, Shamsul; Uddin, Md. Wares; Islam, K. M. Tarikul; Hasan, Mahmudul (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 15-year-old male hailing from Khagrachhari was admitted into the department with the complaints of swelling on the right side of face for 10 months with recurrent severe epistaxis, progressive proptosis, unilateral nasal obstruction and impairment of hearing for two months. On extraoral examination, there was a firm non-tender, nonmobile, fixed swelling on the right side of cheek causing facial asymmetry measuring about 10 × 12 cm in size extending from upper eyelid to middle of the right cheek supero-inferiorly and pre-auricular area to the medial wall of nose postero-anteriorly